Metformin increases protein expression of Bax and p21 in WiDr cancer cell line - Mahanani, Melani Ratih; Budiani, Dyah Ratna; Probandari, Ari Natalia (Nexus Kedokteran Translasional, 2015)
Background: Colorectal cancer is malignancy in the gastrointestinal tract which leads to high morbidity and mortality rates globally. Colorectal cancer is the fourth highest cancer in Indonesia. 5-Fluorouracil (5-FU) is the first choice of chemotherapy for treating colorectal cancer but this therapy isless effective due to severeadverse effects. Metformin, a biguanidediabetes drug, has a potential anticancer, which is able to inhibit growth of some cancer cell lines like breast cancer, prostate cancer, hepatocellular cancer, and nasopharynx cancer. The aim of this study was to investigate protein expression ofBax (pro apoptotic protein) and p21 (cell cycle inhibitor) on colorectal cancer cell line treated with metformin. Methods: This study was a laboratory experimental study with the posttest only control group design. WiDrcancer cell line was cultured in RPMI1640 medium supplemented with 10% fetal bovine serum, 100 U penicillin and 100 Âµg/ml streptomycin and incubatedin 5% CO2for 48 h at 37 Â° C.Following day, cellswere treated with medium only, 7.68 mM5-FU and various doses of metformin(20, 10 and 5 mM) respectively. Protein expression of Bax and p21 was assessed by using immunocytochemistry staining against monoclonal antibodies antihuman Bax and p21.Intensity staining of each cell group was cytological scored and statistically analyzed by using Kruskal Wallis test. Results:Higher intensity score of Bax immunostaining was observed in WiDr cell line treated with three doses of metformin, compared to that of incontrol WiDr cell line and reached significantly difference with p= 0,00. Interestingly, these intensity scores of immunostaining were higher than the intensity score of immunostaining in WiDr cell line with 5-FU treatment. Moreover, administration of metformin increased intensity staining score against p21 monoclonal antibody with negatively dose dependent manner. WiDr cell line administered with 5 mM metformin had the highest intensity score of immunostaining but the intensity score was lower than the intensity score of immunostaining in WiDr cell line with 5-FU treatment. Conclusion: Metformin up regulates protein expression of Bax and p21 in WiDr cancer cell line and may become a promising anticancer. Further investigation is required to confirm the up regulation of both proteins. Keywords: Bax,colorectal cancer, metformin, p21Â